PENYERAPAN TIMBAL (Pb) PADA SISTIM ORGAN IKAN MAS (Cyprinus carpio L) - Yusni Ikhwan Siregar; Adel Zamri; Helmi Putra (Program Pascasarjana Universitas Riau, 2012)
A study on the uptake of Pb in the organ system of carp was carried out in the laboratoryscale. The research aims to identify the uptake rate of Pb in the gill, intestine and muscle ofthe fish. A completely randomized design was done in the experiment laboratory with threetreatments and three replications. The total of 120 fish were exposed to three concentrationsof Pb (1, 3 and 5 ppm of PbNO3) in nine aquarium for 168 hours. Pb concentration in the organsystem of fish were analyzed at 24, 96 and 168 hours, respectively. The concentration of Pbin the intestine were 0.29, 0.44 and 0.47 ppm, for 24, 96 and 168 hour exposure, respectively.Meanwhile, Pb content in the gill were 0.21, 0.39 and 0.45 ppm, respectively. It revealed thatPb concentration in all organs of fish increased significantly (P<0.05) following increased ofexposure time.